2019
DOI: 10.1017/s0022109019000097
|View full text |Cite
|
Sign up to set email alerts
|

Good Volatility, Bad Volatility, and the Cross Section of Stock Returns

Abstract: Based on intraday data for a large cross section of individual stocks and newly developed econometric procedures, we decompose the realized variation for each of the stocks into separate so-called realized up and down semi-variance measures, or “good” and “bad” volatilities, associated with positive and negative high-frequency price increments, respectively. Sorting the individual stocks into portfolios based on their normalized good minus bad volatilities results in economically large and highly statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 66 publications
23
83
0
Order By: Relevance
“…However, neither of SJt and IVAt are significantly correlated with excess returns at intermediate and low frequencies. The significantly negative risk‐return relation for SJt in the short run is in agreement with the results of Bollerslev et al (2019). The long‐run correlations between variance differences and returns are also depicted in Figure 1, where VRPt,VRPtU, and VRPtD generally display strong comovements with returns.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…However, neither of SJt and IVAt are significantly correlated with excess returns at intermediate and low frequencies. The significantly negative risk‐return relation for SJt in the short run is in agreement with the results of Bollerslev et al (2019). The long‐run correlations between variance differences and returns are also depicted in Figure 1, where VRPt,VRPtU, and VRPtD generally display strong comovements with returns.…”
Section: Resultssupporting
confidence: 92%
“…In addition, our simulation supports the empirical evidence of the inferior performances of the SJt and IVAt in predicting returns, especially for intermediate and long horizons after h>9. The nature of the SJt as a short‐lived return predictor is discussed in Bollerslev et al (2019), who show that the SJt only predicts returns at weekly horizons and raise concerns regarding the role of SJt as a priced risk factor.…”
Section: Simulationsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, decomposition of volatility into short-run and long-run when determining asset premium was proven to be useful as well (Adrian and Rosenberg, 2008). Moreover, Bollerslev et al (2016) incorporated notion of downside risk into concept of volatility risk and showed that stocks with high negative realized semivariance yield higher returns. Farago and Tédongap (2017) examine downside volatility risk in their five-factor model and obtain model with negative prices of risk of volatility downside factor yielding low returns for assets that positively covary with innovations of market volatility during disappointing events.…”
Section: Extreme Volatility Riskmentioning
confidence: 99%